PENGGUNAAN METAFORA KEMATIAN DALAM MASYARAKAT LOLI - Djawa, Alex (Jurnal Lazuardi, 2025)
The death of a person for the Loli community is a social and cultural event. It is not surprising that every person's death is usually mourned for days or weeks. In lamentations, expressions denoting the dead are often used. With the wailing it could be seen that the dead was a baby with the expression tollu 'egg' which had been broken. If a young person who dies is depicted with broken rice, his hair is still black, and his teeth are still white, while an old person is depicted with rotten roots and a rotten tree. That is a metaphor in the socio-cultural Loli community.